Positive health : designs for action - Beyrer, Mary K.; Cushman, Wesley P. (Philadelphia : Lea & Febiger, 1977)
Discusses health problems facing young adults, including sexuality, drugs, nutrition, disease, and pollution.
Original ed., 1965 by W. P. Cushman and others.
Includes bibliographies and index.
Keywords: Health; Public health; Health; Public health